2012
DOI: 10.1097/pcc.0b013e3182191a35
|View full text |Cite
|
Sign up to set email alerts
|

Right-to-left shunting in the ductus arteriosus is induced readily by intense crying and rapid postural change in neonates with meconium-stained amniotic fluid*

Abstract: Right-to-left shunting in the ductus arteriosus may be induced readily by intense crying and rapid postural change in infants with meconium-stained amniotic fluid. It is important to monitor SpO2 at both pre- and postductal regions until 120 mins after birth in neonates with meconium-stained amniotic fluid and to subject these infants to minimal manipulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Also, Dinwiddie et al [15] demonstrated in 1- to 3-day-old infants with respiratory distress syndrome that the cry resembles a Valsalva maneuver with a decrease in systemic blood pressure. It has been described that a Valsalva maneuver increases the pulmonary blood pressure [9]. Although we studied infants with healthy lungs in transition, it is probable that an increase in the RtoL DA shunt occurs during the expiratory phase of crying.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Dinwiddie et al [15] demonstrated in 1- to 3-day-old infants with respiratory distress syndrome that the cry resembles a Valsalva maneuver with a decrease in systemic blood pressure. It has been described that a Valsalva maneuver increases the pulmonary blood pressure [9]. Although we studied infants with healthy lungs in transition, it is probable that an increase in the RtoL DA shunt occurs during the expiratory phase of crying.…”
Section: Discussionmentioning
confidence: 99%
“…There is little data on the effect of crying on hemodynamics during the fetal to newborn transition. Baba et al [9] observed an increase pre-post ductal difference in oxygen saturation during crying in infants with meconium aspiration syndrome several hours after birth, which may indicate that crying influences the DA shunt for up to several hours after birth.…”
Section: Introductionmentioning
confidence: 99%
“…Crying is a distress signal (Christensson, Cabrera, Christensson, Uvnas-Moberg, & Winberg, 1995), probably elicited by sudden bright light (babies born in the dark hardly cry), and prolonged by maternal-neonate separation (Michelsson, Christensson, Rothganger, & Winberg, 1996). Crying is not helpful for breathing, rather the opposite as it restores the fetal circulation (Baba et al, 2012;Ludington-Hoe, Cong, & Hashemi, 2002). Transition to extrauterine life begin in the first seconds of life, and includes an array of physiological adjustments, including using the lungs for the first time.…”
Section: Distinguishing Nurturescience From Neurosciencementioning
confidence: 99%